Entrepreneurial information search - Cooper, Arnold C.; Folta, Timothy B.; Woo, Carolyn (Journal of Business Venturing, 1995)
Information is a key resource for the new venture. Despite the importance of information search practices, little research has examined whether entrepreneurs show a tendency to search for more or less information under particular conditions. This article considers whether information search might be explained by concepts of bounded rationality. Such theories lead to the counterintuitive expectation that entrepreneurs with less experience or those entering unfamiliar fields would search less because of their more limited understanding of what is needed. In addition, entrepreneurs with higher levels of initial confidence would search less because their “entrepreneurial euphoria” may limit their ability to assess their own needs for additional information. This study examined the information search practices of 1176 entrepreneurs. It considered six sources of information that were widely used: accountants, friends or relatives, other business owners, bankers, lawyers, and generally available books and manuals. Three measures of search intensity were developed, with the first reflecting the relative importance of all six sources and the remaining two focusing upon the subcategories of professional and personal sources. It was found that those who had no entrepreneurial experience, on the average, sought more, not less, information. However, as expected, those who ventured into fields which were different and those who had higher levels of initial confidence sought less information. An interaction effect provides insight into these findings and reveals that inexperienced entrepreneurs varied their search depending upon whether they were in familiar or unfamiliar domains. In particular, novice entrepreneurs searched less extensively in unfamiliar domains, a behavior consistent with bounded rationality. By contrast, experienced entrepreneurs did not vary their search pattern. It was also found that entrepreneurs having high levels of confidence sought less information, as expected. The behavioral tendencies observed here appear to have clear implications for entrepreneurs and their advisors. We might expect that those venturing into fields they do not know would have more to learn and thus would search more aggressively. However, neither inexperienced nor experienced entrepreneurs acted in this way. In fact, inexperienced entrepreneurs lessened their search as they entered fields they did not know, consistent with the bounded-rationality model. Many prior studies have found that entrepreneurs entering unfamiliar fields are, on the average, less successful (Cooper and Gimeno-Gascon 1992). This certainly raises questions about whether entrepreneurs, both experienced and inexperienced, might benefit from greater emphasis upon gathering and utilizing external information as they enter fields that are new to them. Outside advisors (if the entrepreneur will utilize them) may be helpful in urging and assisting entrepreneurs who enter unfamiliar fields to engage in more extensive information search, even though they may have less developed networks of contacts and less of a feeling for what is needed in such fields. With respect to initial confidence, entrepreneurs and their advisors should recognize that high levels of confidence may lead to lower levels of information search. Recognizing this tendency, they should use care to ensure that entrepreneurial euphoria does not lead to blinders in the search for information.